Study of the hydrogen diffusion out of press hardened boron steel - Hortlund, Hanna (2009)
This master thesis was performed at the R&D department at Gestamp HardTech AB in Luleå. Gestamp HardTech is a global leader in the development and manufacturing of safety components for the automotive industry and the production is based on the press hardening technique. Hydrogen is known to cause degradation of steel and this may be seen as either a decrease in ductility or as spontaneous fracture for internally or externally stressed components. Studies of the hydrogen diffusion out of steels are of great importance for the steel industry as this provides more knowledge about the hydrogen degradation phenomenon and better possibilities of preventing problems caused by hydrogen. The purpose of this thesis was to study how the diffusible hydrogen content in uncoated, Al-Si pre-coated and zinc electroplated boron steel changes with time after press hardening. The influence of post heat treatments on the diffusible hydrogen content was also examined. In order to study the hydrogen diffusion out of boron steel, hydrogen was introduced into sample pieces. The introduction methods were electrochemical charging, charging in a laboratory furnace by varying the dew point temperature and zinc electroplating. The samples were then stored at room temperature and heat treated to accelerate the hydrogen diffusion out of the samples. Hydrogen charging in a furnace by varying the dew point temperature was established to be the most suitable charging method. Linear correlations between the diffusible hydrogen content in the samples and the dew point temperatures in the furnace were found. The hydrogen diffusion behavior of press hardened boron steel proved to be different for uncoated, Al-Si pre-coated and zinc electroplated boron steel. Post heat treatments were shown to be effective in accelerating the hydrogen diffusion out of Al-Si pre-coated and zinc electroplated boron steel. Validerat; 20101217 (root)